PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE SYNERGETIC TEACHING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 20 PADANG - Ningsih, Nini Gusma (STKIP PGRI Sumbar, 2014)
This research is motivated by the students understanding of mathematicalconcepts is low, it can see from the result of students learning process SMPN 20Padang. The aim of this research to determine whether the application by usingactive learning strategies Synergetic Teaching effect on the understanding ofmathematical concepts in class VIII 20 Padang. Type of research is the study ofPre-Eksperimental research designed with Pre-Test and Post-Test Group.Population in this study was a class VIII SMPN 20 Padang 2014/2015 academicyear, to take sample is randomly that is VIII.6 as sample class. The instrumentused in this is the initial test (Pre-Test) and final test (Post-Test) in the from ofdata used essay. The analysis test t-test. Based on the analysis of data obtained,so that the research hypothesis can be concluded that there are significantapplication of learning strategies Synergetic Teaching to the understanding of themathematical concept of class VIII SMPN 20 Padang.